Pendekatan Kontekstual dalam Meningkatkan Penguasaan Konsep Bangun Ruang - Mawarni Mawarni (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
This study aims to improve student mathematics learning outcomes on the topic of solid figure through the implementation of contextual approach. This research is a classroom action research (CAR) conducted in class VI B SDN 139 / V PKMT Taman Raja. Subjects in this study were 29 students. Students have difficulty in the process of abstraction of mathematical concepts and tend to be less motivated to learn. In applying the contextual approach, students are given problems that are often encountered in everyday life and collaborative learning. The results showed that students experienced an increase in mastery of concepts as indicated by an increase in the average score of 21.61 in the pre cycle, 57.47 in the first cycle, and 79.77 in the second cycle.